2006
DOI: 10.1149/1.2200297
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Vertical Sidewalls in GaAs∕AlGaAs Heterostructure Using Light-Induced Wet Etching

Abstract: We investigate the effects of light-induced wet etching ͑LIWE͒ on sidewall profile and etch rate for n-and p-type GaAs bulk, epitaxial AlGaAs layers and two different types of laser heterostructure using three different etch masks and three light-emitting diodes as light sources. The experiments show that the LIWE parameters ͑light-source wavelength, mask conductivity, sample layer structure͒ control the sidewall angle and etch rate. The technique successfully produced vertical sidewalls and "on-demand" etch-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In this connection, it has been proposed that the side profile of semiconductor heterostructures is mainly influenced by the charge carrier concentration in the various layers in the layer stack [13]. Further factors considered for achieving smoother side profiles include modification in wet etchant composition, optimising etching conditions such as temperature, the viscosity of the etchant and its agitation [14], as well as etch mask conductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, it has been proposed that the side profile of semiconductor heterostructures is mainly influenced by the charge carrier concentration in the various layers in the layer stack [13]. Further factors considered for achieving smoother side profiles include modification in wet etchant composition, optimising etching conditions such as temperature, the viscosity of the etchant and its agitation [14], as well as etch mask conductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In semiconductor manufacture, the challenge is to control the photoetching process with a micro-and nanometer accuracy. Both focused laser beam 7,9,21,22 and light mold 8,11,12 are adopted for this purpose. However, the working electrolytes usually contain strong oxidants with strong acid [7][8][9]11,23 or alkali environment, 12,24,25 e.g., the H 2 O 2 /H 2 SO 4 solution, in which the semiconductor materials can be spontaneously corroded.…”
Section: Introductionmentioning
confidence: 99%
“…When the semiconductor is illuminated, the charge separation results in local bipolarity. In the presence of appropriate electrolyte, the photogenerated holes would oxidize the reductive species in solution or the semiconductor itself if the photogenerated electrons were removed by electron acceptors. On the basis of this photocorrosion phenomenon, photoetching techniques have been developed to fabricate three-dimensional micro- and nanostructures (3D-MNSs) directly on semiconductor wafers. For example, porous silicon roughened by photoetching process can enhance light-harvesting efficiency and improve the photoelectric conversion efficiency. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser-induced etching, an improved etching process, is very much needed in the fabrication of III-V integrated optic and microelectronic devices (Syvenkyy et al 2005;Veiko et al 2005;Yi and Parker 2006). Several studies of laser induced etching have shown the importance of its higher processing rate than the conventional etching techniques (Svorcik and Rtybka 1989;Cha et al 1997;Han et al 1998;Simkiene et al 2003).…”
Section: Introductionmentioning
confidence: 99%